The portrayal of gender in Marvel and Star Wars media targeted towards children - Clarke, Lucy Louise; Hine, Benjamin (Frontiers in Sociology, 2024)
An abundance of previous research has investigated how gender has been portrayed within feature length films produced by Walt Disney Animation Studios, particularly those within the Disney princess franchise. However, the Disney corporation acquired the Marvel and Star Wars franchises in 2009 and 2012, respectively, which was likely a strategy for the corporation to obtain characters that would capture the imagination of boys and men. The current qualitative study explored how gender is portrayed by leading protagonists in these texts, utilising thematic analysis, which was necessary considering little is currently known in this domain. The researchers analysed series one of Avengers Assemble and series one of Star Wars Rebels. Interpretation of the data led to the development of several themes and subthemes based on the gendered portrayals within each series. Overall, the findings suggest that there was more overt gender stereotyping in Avengers Assemble when compared with Star Wars Rebels, meaning that the former could be particularly problematic for children who may replicate its messages. The current study has facilitated a greater understanding of the gendered messages that may be consumed by children who engage with Marvel and Star Wars media. Future research is needed to assess the relationship between such messages and children’s behaviour.